Asbabun Nuzul dalam Perspektif Pendidikan - Iin Kendedes (Jurnal Al Bayan: Jurnal Jurusan Pendidikan Bahasa Arab)
Asbabun nuzul is one aspect of important domains within the disciplines of Quranic studies by which a sound understanding of Islam possibly occurs. The practices of educatin, in another side, play an urgent and stategic role for enhanching the quality of human resources within muslim community. This article elaborates the importance of teachers’ roles—or the practices of Islamic education in general—in explaining asbabun nuzul and discloses the strategic correlation between students’ understanding of asbabun nuzul and the quality of education as well.